Parenting Patterns of Parents in Realizing Attitudes of Love The Qur’an in Early Childhood - Haslin, Muh Ilham Nur (S&Co Publishing, 2024)
Family education has a very important role in shaping a child's personality, especially in early childhood education. Because early childhood education is the basis for introducing Islamic personality values from an early age. The aim of this research is to describe parenting patterns in fostering an attitude of love for the Koran in young children in Kajuara, Lempang Village, Tanete Riaja District, Barru. This research uses qualitative methods and a phenomenological approach to describe data from situations that occur directly. Data was collected through interviews, observation and documentation. The results of the research show that the description of parenting patterns in realizing an attitude of love for the Qur'an in early childhood in Kajuara, Lempang Village, Tanete Riaja District, Barru Regency is carried out in several stages, namely, the exemplary method, the habituation method, the advice method, the punishment method, Prize or prize method. The dominant method used by parents in Kajuara, Lempang Village, Tanete Riaja District is the method of habituation and example. This method is considered the most effective in creating an attitude of love for the Qur’an.